2007
DOI: 10.1159/000103209
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects on the Activation of the Auditory Cortex during Binaural Speech Listening in White Noise: An fMRI Study

Abstract: The functional significance of age-related pathology of the auditory cortex is not well established. The purpose of this study was to elucidate the activation pattern of the auditory cortex in aged subjects in response to speech signals. Functional magnetic resonance imaging was performed on 12 elderly subjects with normal hearing acuity during selective listening with both ears to speech sounds in quiet and in white noise. Twelve young, normal-hearing subjects served as controls. Our results showed that activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 44 publications
1
38
1
Order By: Relevance
“…In general, when listeners are tested in less challenging situations, the role of central processing is reduced compared with when they are tested in more adverse situations. Recent physiologic studies have shown that listeners who can recruit a wider network of prefrontal cortical activity to compensate for listening in adverse environments generally perform better than listeners who do not adapt in a similar manner (Hwang et al, 2007; Wong et al, 2009). Indeed, Wong et al (2009) also reported that for both young and older listeners, the ability to recruit a greater region of cortical activity had a significant correlation with behavioral performance for speech-processing tasks in noise.…”
Section: Discussionmentioning
confidence: 99%
“…In general, when listeners are tested in less challenging situations, the role of central processing is reduced compared with when they are tested in more adverse situations. Recent physiologic studies have shown that listeners who can recruit a wider network of prefrontal cortical activity to compensate for listening in adverse environments generally perform better than listeners who do not adapt in a similar manner (Hwang et al, 2007; Wong et al, 2009). Indeed, Wong et al (2009) also reported that for both young and older listeners, the ability to recruit a greater region of cortical activity had a significant correlation with behavioral performance for speech-processing tasks in noise.…”
Section: Discussionmentioning
confidence: 99%
“…But some recent findings in relation to binaural function and ageing could be of relevance to the outcome with bilateral implantation observed here. Recent studies (26, 27) report that in elderly listeners with clinically normal peripheral hearing function, there are signs of reduced binaural ability resulting in poorer speech recognition in noise compared with younger listeners. One of these (27) also found reduced activation in the bilateral superior temporal gyrus in members of their older sample.…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not reflect the more advanced central functions, such as those of the central auditory cortex. The temporal resolution of functional magnetic resonance imaging is close to 1 s and is therefore not suitable for the real-time reflection of central auditory processing [Hwang et al, 2007]. Auditory event-related potentials are potentials recorded from the scalp with a high temporal resolution and are accurate to the millisecond.…”
mentioning
confidence: 99%